Projeto poliedu: desenvolvimento político educacional - BONJORNE, Anne Lourenço; SILVA, Beatriz Figueredo; SILVA, Jenifer Araújo Santos; SANTOS, Valentine Fabrice Vinciguerra dos; BARTALINI, Yasmin Alves (186, 2022)
O trabalho confeccionado tem como principal objetivo aprimorar o senso crítico e conhecimento político do povo brasileiro através da empresa PoliEdu, que é voltada para a educação política de maneira acessível e simplificada para todos. A empresa criada pretende garantir que política não seja tratada como algo irrelevante na sociedade, incentivando seus alunos a debaterem sobre assuntos recorrentes no meio político brasileiro, entender os cargos e atribuições de cada candidato.

The work made has as its main objective to improve the critical sense and political knowledge of the Brazilian people through the company PoliEdu, which is focused on political education in an accessible and simplified way for everyone. The company intends to ensure that politics is not treated as something irrelevant in society, encouraging its students to debate recurring issues in the Brazilian political environment, understanding the positions and attributions of each candidate
Poliedu project: educational policy development
Keywords: Educação política; Empresas; Gestão e Negócios